(untitled) (Principles and Practice of Clinical Research, 2021)
Abstract Introduction: The unprecedented, worldwide COVID-19 pandemic demanded the need for adequate personal protective equipment (PPE) for health care workers (HCWs). The commonly recommended N95-mask (N95) needs further optimization in the areas of technology, re-usability, and comfort. The LEAF-mask (LEAF) reportedly offers improved technology and innovative features, however, neither of them have been tested yet. Therefore, there is an ongoing need to study the efficacy of masks used by HCWs in the intensive care units (ICUs). The goal of this study is to demonstrate the superiority of LEAF for nurses working in COVID-19 ICUs when compared to the N95.Methods: A phase-II, multicenter, randomized, controlled, open-label, clinical trial. A sample size of 98 nurses, working in COVID-19 ICUs, will be necessary to detect a significant difference in viral load of the inner and outer parts of both masks as the primary outcome. Secondary outcomes will be exploratory in nature, including adverse effects, wearing comfort of masks, and virus infection rate.Discussion: The ongoing COVID-19 pandemic has already infected and killed millions of people and burdens healthcare systems worldwide. This led to the search for comprehensive measures to prevent the further spread of the SARS-CoV-2, in particular among HCWs in the frontline. Therefore, this study intends to demonstrate the superiority of the new LEAF compared to the N95, primarily in efficacy but also in re-usability and wearing comfort when used by nurses in COVID-19 ICUs. The possible findings from this study on improved technologies and innovative features possibly shown in the LEAF may greatly contribute to better working conditions for nurses working in COVID-19 ICUs.